Comparison of netupitant/palonosetron with 5-hydroxytryptamine-3 receptor antagonist in preventing of chemotherapy-induced nausea and vomiting in patients undergoing hematopoietic stem cell transplantation - Zhang, Hang; Zeng, Qiang; Dong, Tian; Chen, Xinchuan; Kuang, Pu; Li, Jian; Wu, Qiuhui; Liu, Ting; Niu, Ting; Liu, Zhigang; Ji, Jie (Frontiers in Oncology, 2023)
Background The use of 5-hydroxytryptamine-3 receptor antagonists (5HT3RA) has long been considered the standard regimen for preventing chemotherapy-induced nausea and vomiting (CINV) prior to hematopoietic stem cell transplantation (HSCT). However, their therapeutic outcomes have been unsatisfactory. NEPA, an oral formulation combining the neurokinin-1 receptor antagonist netupitant and the 5HT3RA palonosetron, has received regulatory approval for the management of highly and moderately emetogenic chemotherapy. This study aims to compare the efficacy of NEPA with that of 5HT3RA alone in preventing CINV among patients undergoing multiday conditioning chemotherapy prior to HSCT. Patients and methods We conducted a retrospective analysis of patients who underwent HSCT between September 2019 and September 2022. Efficacy outcomes were assessed based on the rates of patients achieving complete response (CR: no emesis and no use of rescue medication), complete control (CC: CR without significant nausea), no vomiting, and no significant nausea. Results The NEPA group consisted of 106 patients, while the 5HT3RA group included 107 patients. The NEPA group exhibited significantly higher rates of CR compared to the 5HT3RA group during the overall phase (71.7% vs. 32.7%, P<0.001), acute phase (78.3% vs. 43.0%, P<0.001), and delayed phase (84.9% vs. 58.9%, P<0.001). Similarly, rates of CC, no vomiting, and no significant nausea were significantly better in the NEPA group across all phases (P<0.001). Conclusion NEPA demonstrated superior efficacy compared to 5HT3RA in preventing CINV during all phases of multiday conditioning regimens among patients undergoing HSCT.